The impact of self-care behavior on quality of life among patients with heart failure in Malaysia: a cross-sectional study - Mohamad, Norfidah; Mulud, Zamzaliza Abdul; Chan, Chong Mei; Razak, Hairil Rashmizal Abdul; Esa, Nor Masita (Jurnal Ners, 2025)
Introduction: Individuals with heart failure anticipate adjustment to self-care behaviors following hospital discharge. Self-care in heart failure includes medication adherence, dietary modifications, symptom monitoring, and activity adjustment. Adequate self-care behavior may contribute to enhanced outcomes, decreased hospitalization, and improved quality of life in patients with heart failure. This study aimed to determine the level of self-care behavior, quality of life, and its relationships among patients with heart failure. Methods: A cross-sectional study using purposive sampling was conducted among 200 heart failure patients at a teaching hospital in Selangor, Malaysia. The sample size was determined using G*Power to ensure adequate statistical power. Data were collected using the Self-Care of Heart Failure Index (SCHFI) and the Minnesota Living with Heart Failure Questionnaire (MLHFQ). Descriptive statistics, Pearson’s correlation, and multiple linear regression were used in this study. Results: The results indicated that the total mean score of self-care behavior was 145.42 and SD=16.23. Most patients demonstrated good quality of life (n=73, 36.5%), moderate quality of life (n=62, 31%), and poor quality of life (n=65, 32.5 %). Pearson's correlation revealed a significant (p<0.001) correlation (r = 0.651) between self-care behavior and quality of life. Conclusions: In conclusion, this study demonstrated that higher levels of self-care are associated with better quality of life in patients with heart failure. It is recommended that nurses provide individualized self-care education at discharge, focusing on medication adherence, symptom monitoring, and lifestyle changes to improve quality of life.